The Influence of e-WOM and Online Media Regarding the Dangers of Matcha Consumption on Matcha Drink Purchase Decisions in Mataram City Mediated by Health Awareness - Ni Nyoman Jingga Sukmarani; Lalu Edy Herman Mulyono (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of electronic word of mouth (e-WOM) and online media regarding the dangers of matcha consumption on matcha beverage purchasing decisions in Mataram City, with health awareness as a mediating variable. The background of the study is based on the increasing consumption of matcha beverages amidst the proliferation of digital information regarding its health impacts spread through online media and consumer reviews. This study used a quantitative approach with a survey design. The sample consisted of 80 respondents selected using a purposive sampling technique. The criteria were domiciled in Mataram City, had consumed matcha beverages, and had been exposed to matcha information through online media. Primary data were collected through an online questionnaire using a 1-5 Likert scale and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results showed that e-WOM and online media had a positive and significant influence on purchasing decisions. Health awareness also had a positive and mediating effect on the influence of e-WOM and online media on purchasing decisions. This study concluded that digital information and health awareness play a significant role in shaping matcha beverage purchasing decisions.